Consumer behaviour and segmentation of - Posthumus, Corna (My University, 2011)
The South African government has embarked on a minerals beneficiation drive, as evident from recent legislative changes, to address South Africa’s shortcomings in adding value to mined raw materials (precious metals and gemstones). This favourable business climate created for local jewellery manufacturers poses a challenge to marketers to first understand local jewellery consumers’ buying behaviours and attitudes before branding these jewellery items across different market segments. The above provided an impetus for conducting a consumer research into South Africa’s somewhat immature precious jewellery market. A structured standard questionnaire was designed to determine consumer demographics, behaviours and attitudes towards precious jewellery. The purpose of the research study was twofold. First, typical jewellery consumers’ buying behaviour, shopping preferences and attitudes were determined to segment the South African precious jewellery market. These findings (which were analysed using quantitative research methodologies) led to the second part of the study, i.e. developing a brand strategy framework to reach the identified market segments. The results showed that the typical precious jewellery consumer in South Africa is: a primarily white, “twenty-something to thirty-something” high-income female. The results also indicated that local buying behaviours and shopping preferences (i.e. the where, what, how, when and how) of precious jewellery are very similar to those cited for overseas jewellery consumers. However, the study revealed that there are two meaningful market segments in South Africa’s precious jewellery market, as opposed to four segments, cited in the literature. The characteristics of the first segment are very similar to those documented for overseas market segments. However, an unexpected second segment (which is not documented in the literature) emerged from the study, reflecting the differentiating characteristics of the typical South African jewellery consumer, i.e. impulsive buyers of massproduced, low-priced, fashion precious jewellery items. Brand strategy frameworks for both market segments were then developed based on the study’s attitudinal segmentation results
MBA - WBS
Keywords: Consumer behaviour; Consumer segmentation; Jewellery